Post-traumatic stress and resilience in health professionals working in the Covid-19 period - قيرع حاتم , وهيبة; براهمي, سيلية; شلهاب, أوردية (مجلة دراسات في سيكولوجية الانحراف, 2022)
The aim of this research is to describe the traumatic effect of the COVID-19 health crisis and the resilience of health professionals intervening during this period. This study concerned 32 cases practising at the Public Hospital Establishment of Kheratta (Bejaia). To achieve the objectives of this research, we used a semi-structured interview, the PTSD Checklist For DSM-5 (PCL 5), and the Wagnild and Young resilience scale (RS-R). The results showed that 74.1% of the health professionals participating in the research had symptoms of posttraumatic stress and that 29% of them showed a moderate degree of resilience. This moderate ability to emerge from this health crisis raises the alarm about the urgent need for psychological support for health professionals confronted with this traumatic COVID-19 pandemic.